Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/1097-0355(199121)12:1<17::aid-imhj2280120103>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parent, child, and contextual factors on the quality of the home environment

Abstract: The purpose of this study was to examine factors related t o the quality of the home environments mothers provide for their infants. Data from the National Longitudinal Survey of Youth on 602 mothers with infants between 12 and 23 months of age were used for this study. Consistent with Belsky's model of the determinants of parenting, the quality of the home environment was influenced by maternal characteristics, child characteristics, and contextual factors. A positive linear relation was found between scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This is consistent with the findings from other studies using samples from the U.S. (Baharudin, 1992;Hannan & Luster, 1991;Menaghan & Parcel, 1991). However, number of children in the family was significantly correlated with only one of the subscales of the HOME, physical environment (-.44); contrary to expectations, family size was unrelated to the subscales tapping language stimulation or academic stimulation (see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings from other studies using samples from the U.S. (Baharudin, 1992;Hannan & Luster, 1991;Menaghan & Parcel, 1991). However, number of children in the family was significantly correlated with only one of the subscales of the HOME, physical environment (-.44); contrary to expectations, family size was unrelated to the subscales tapping language stimulation or academic stimulation (see Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…For mothers of healthy infants, maternal child care competence has been associated with parenting outcomes such as quality of mother-infant interaction (Teti & Gelfand, 1991), occurrence of child abuse (Brayden, Altemeier, Tucker, Deitrich, & Veitz, 1992;Mash, Johnston, & Ovitz, 1983), and amount of cognitive stimulation provided in the home (Hannon & Luster, 1991;Secco, Ateah, Woodgate, & Moffatt, 2002). The significant relationship between depression and maternal toddler care competence, measured as selfefficacy caring for a healthy toddler (Gross, Conrad, Fogg, & Wothke, 1994;Teti & Gelfand, 1991), underscores the need to examine depression among parents of biologically vulnerable toddlers.…”
Section: Maternal Characteristicsmentioning
confidence: 99%
“…Studies of adolescent mothers have revealed significant relationships among age, social support, child health (Boyce, Chesterman et al, 1991), maternal attitudes and the parenting role (Ragozin, Basham et al, 1982;Hannon & Luster, 1991). Older mothers have more favorable maternal self-efficacy, parenting competence, and performed mothering (Landy, Clark et al, 1983;Garcia Coll, Hoffman et al, 1987;Stevens, 1988;Dormire, Strauss et al, 1989), suggesting the importance of age or factors associated with age.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cross-sectional studies have demonstrated that adolescent mothers, compared with older mothers, have less favorable psychosocial well being, personal attributes (Landy, Clark et al, 1983;Stevens, 1988;Dormire, Strauss et al 1989;Boyce, Chesterman et al, 1991), and performed mothering behavior (Levine, Garcia Coll et al, 1985;Carlson, Labarba et al, 1986;Garcia Coll, Vohr et al, 1986;VonWindeguth and Urbano, 1989). Longitudinal studies have shown significant associations between psychosocial well being and mother-infant relationship quality, child cognitive development (Barlow & Coren, 2001), and performed mothering (Hannon & Luster, 1991). Negative developmental outcomes are more common among children born to adolescent mothers (Brooks-Gunn & Furstenberg, 1986;Carlson, Labarba et al, 1986;Furstenburg, Brooks-Gunn et al, 1987;Hardy & Zabin, 1991;Chase-Lansdale, Brooks-Gunn et al, 1992).…”
mentioning
confidence: 99%